2018
DOI: 10.5324/nordis.v0i23.2464
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Static Breakdown Voltage of the Lubricating Film in a Mechanical Ball Bearing

Abstract: <p>In this paper, the current pulse (discharge) activity in a small bearing is investigated when current-limited DC voltages of different levels are applied to the shaft under varying rotational speeds and mechanical loads. The measurements show that the inception voltage of discharges in the bearing is higher than the extinction voltage. However, when the discharge activity has been intense the bearing exhibits difficulties to recover its insulating properties when the voltage is decreased to a low volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When the bearing voltage exceeds the isolating capacity of the lubricating film, an electric discharge occurs in the form of an arc between the rings and the rolling elements. The aforementioned isolating capacity of the lubricating film depends on the lubricating film thickness and the breakdown field strength of the lubricant [20,21]. This shows that the lubricant used in the bearing thus has a crucial influence on the occurrence of EDM currents.…”
Section: Electric Discharge Machining (Edm) Breakdowns and Edm Currentsmentioning
confidence: 99%
“…When the bearing voltage exceeds the isolating capacity of the lubricating film, an electric discharge occurs in the form of an arc between the rings and the rolling elements. The aforementioned isolating capacity of the lubricating film depends on the lubricating film thickness and the breakdown field strength of the lubricant [20,21]. This shows that the lubricant used in the bearing thus has a crucial influence on the occurrence of EDM currents.…”
Section: Electric Discharge Machining (Edm) Breakdowns and Edm Currentsmentioning
confidence: 99%
“…The investigations by Harder [17] and Joshi [18] show that rolling bearings have a higher susceptibility to current passage after the first electrical breakdown (initial breakdown). On the one hand, this may be due to the roughened surface caused by the initial damage, because the resulting roughness peaks mean that a homogeneous electric field can no longer be assumed between the contact partners, and breakdowns occur more quickly due to the field elevation there [17].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study conducted by Joshi and Blennow [10] on the electrical properties of lubricants showed that the number and duration of current discharge events was dependant on the voltage, shaft speed and bearing load. Bechev et al [11] conducted an analysis of lubricant properties for use in electric motor bearings.…”
Section: Introductionmentioning
confidence: 99%